Agronomic performance of durum wheat (Triticum turgidum L.) possessing the 1BL-1RS translocation cultivated at Mediterranean environments - Zarco-Hernández J.; Michelena A.; Peña R.J. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
At CIMMYT, the 1BL-1RS chromosome substitution has been incorporated to durum wheat germplasm (T. turgidum L.). Research about the effect of 1RS arm on agronomic performance of this durum wheat germplasm is very limited. Therefore, the objective of this study was to evaluate the yield performance of near-isogenic lines from durum wheat 'Altar 84', four carrying 1BL-1RS translocation and four without the translocation (normal). These lines were cultivated at four different Mediterranean environments of Spain. The growing conditions were different in each environment and explained the major part of the observed yield-trait variability. In average, the 1BL-1RS genotypes showed higher 1000-kernels than normal ones, but they also showed less number of spikes and grains per square meter. This yield-component compensatory behavior may explain the lack of difference in grain yield between these two genotypic groups. Except for grain yield, no environment by genotype interaction was observed for the yield-related traits. In conclusion, the presence of the 1RS chromosome arm showed no clear advantage in grain yield over the normal durum wheat genotypes.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)